1987
DOI: 10.1099/00207713-37-4-475
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas plantarii sp. nov., the Causal Agent of Rice Seedling Blight

Abstract: Volume 37, no. 2, p. 148, Table 3: Growth at 40°C should read " + " for P. avenue and P. cattleyae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0
2

Year Published

1994
1994
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 0 publications
1
42
0
2
Order By: Relevance
“…One-day-old cells in PS broth medium were negatively stained with 2n0% phosphotungstic acid (pH 6n5) and were observed with a JEM-1010 transmission electron microscope (JEOL). Physiological and biochemical characteristics were examined as described by Nishiyama (1981) and Azegami et al (1987). Dye's medium C (Dye, 1962) and OY medium (Dye, 1968) were used as the basal media for acid production and utilization tests, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…One-day-old cells in PS broth medium were negatively stained with 2n0% phosphotungstic acid (pH 6n5) and were observed with a JEM-1010 transmission electron microscope (JEOL). Physiological and biochemical characteristics were examined as described by Nishiyama (1981) and Azegami et al (1987). Dye's medium C (Dye, 1962) and OY medium (Dye, 1968) were used as the basal media for acid production and utilization tests, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…P. glumae was included in rRNA group TI on the basis of the rRNA-DNA hybridization data of De Vos et al (9). Pseudomonasplantarii was isolated as the causal agent of rice seedling blight by Azegami et al and was shown to be related to P. gladioli (3). Recently, the rRNA sequences of several Pseudomonas species were studied (7,12,24,40,41,(56)(57)(58)(59), and P. cepacia, a typical species of rRNA group 11, was assigned to the P-purple bacteria (40).…”
Section: P Cepacia P Gladioli ("Pseudomonas Marginata") Pseudomonmentioning
confidence: 99%
“…Burkholderia spp. have been described as plant pathogens (7,21,72), symbiotic rhizospheric or endophytic plant growth promoters (35,130), endosymbionts of fungi (5,56,70) and insects (77,144), and animal pathogens (31,59). They can degrade pollutants (25,30,83,84,147), fix nitrogen and solubilize metals for use by their symbiotic partners (25,73), produce compounds that protect their host-associated partners from pathogenic fungi, bacteria, protozoa, and nematodes (26,111,114), and even induce plant host defense mechanisms (37).…”
mentioning
confidence: 99%